PEÕES DO TRANSPORTE E DO TRECHO: mobilidade do trabalho em Barcarena - Marcel Hazeu; Nádia Socorro Fialho Nascimento; Mylena dos Santos Santana; Ana Caroline dos Santos Ferreira (Revista de Políticas Públicas, 2016)
This paper addresses labor mobility within the logic of super exploitation of the labor in the context of (neo) developmentalism. It aims to analyze the de-re-territorialization of workers by processes of the capitalist advance in the Amazon. Based on a study on social change and labor mobility, empirical research was carried out in the municipality of Barcarena of the state of Pará where the installation of factories and ports transformed the lives of the local community. Concludes that a large number of workers was inserted into the capitalist labor market and transformed into peons of transport and of stretch to ensure their super exploitation. The localities involved became territories of exploitation and transit without any local process that could be called regional development.